THE STRUCTURE OF SUPERIOR BEHAVIOR AND INDIVIDUAL BELONGING BEHAVIOR BASED ON TRUST DEVELOPMENT DIRECTION IN CHINESE FIRMS - Law, Kian Aun; Bhaumik, Amiya; Sun, Peng; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
Abstract -Trust is featured with many merits, for instance, trust is conductive to save the cost of organization management and supervision (Rousseau et al., 1998); trust makes contributions to stimulate positive attitudes of employees, such as organizational commitment, job satisfaction; trust is beneficial to enhance employee performance and behavior, including task performance and organizational citizenship behavior, simultaneously trust also helps to reduce negative work attitudes and behaviors, to cite examples, turnover intention and anti-productive behavior. However, it toils a lot of endeavors to create and maintain trust in an organization. Researchers have paid immense attention to trust, especially the factors that influence the development of interpersonal trust in organizations. This paper, with the core theme of the trust between superior and subordinate in an organization, starts with the trust-oriented superior and subordinate behavior characteristics, and comprehensively expedients the inter-level model of trust development between superior and subordinate in an organization by combining with the factors of organizational control system, to have a deep understanding and research on the dependent variables of trust.